2020
DOI: 10.5505/amj.2020.38268
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of The Coping Attitudes of People with Stroke on Quality of Life

Abstract: Öz Amaç: İnme geçiren bireylerin hastalıkla başa çıkma tutumlarının yaşam kalitesi üzerine olan etkisini incelemektir. Materyal ve Metot: Tanımlayıcı türdeki bu çalışmanın örneklemini Ekim 2018-Haziran 2019 tarihlerinde inme sonrası kontrolleri için bir devlet ve bir eğitim araştırma hastanesinin nöroloji ve fizik tedavi polikliniğine gelen 360 birey oluşturdu. Verilerin toplanmasında sosyodemografik özellikler için oluşturulan anket formu, İnmeye Özgü Yaşam Kalitesi Ölçeği ve Başa Çıkma Tutumlarını Değerlendi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
2
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
1
2
1
Order By: Relevance
“…As behavior modification is based on knowledge, this finding suggests that health education provided to stroke patients is effective in increasing their level of knowledge. The increase in both sleep quality and quality of life scores in stroke patients at the end of the nurse-led training program in this study is consistent with the literature (Akosile et al, 2013;Kes, 2020;Kim et al, 2010;Sonmez & Karasel, 2019).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…As behavior modification is based on knowledge, this finding suggests that health education provided to stroke patients is effective in increasing their level of knowledge. The increase in both sleep quality and quality of life scores in stroke patients at the end of the nurse-led training program in this study is consistent with the literature (Akosile et al, 2013;Kes, 2020;Kim et al, 2010;Sonmez & Karasel, 2019).…”
Section: Discussionsupporting
confidence: 92%
“…Quality of life may be impaired by stroke-related sleep disorders and can be improved by treating these disorders. Previous studies have reported sleep disorders in stroke patients at rates varying between 10% and 50% (Kes, 2020;Kim et al, 2010;Sonmez & Karasel, 2019). Although nearly all of the stroke patients in the intervention group in our study stated that they did not have any sleep-related problems, 43.5% said they felt tired upon waking up in the morning.…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations